The deviant prison: Philadelphia's Eastern State Penitentiary and the origins of America's modern penal system, 1829-1913 - Rubin, Ashley T. (Cambridge historical studies in American law and society, 2021)
Early nineteenth-century American prisons followed one of two dominant models: the Auburn system, in which prisoners performed factory-style labor by day and were placed in solitary confinement at night, and the Pennsylvania system, where prisoners faced 24-hour solitary confinement for the duration of their sentences. By the close of the Civil War, the majority of prisons in the United States had adopted the Auburn system - the only exception was Philadelphia's Eastern State Penitentiary, making it the subject of much criticism and a fascinating outlier. Using the Eastern State Penitentiary as a case study, The Deviant Prison brings to light anxieties and other challenges of nineteenth-century prison administration that helped embed our prison system as we know it today. Drawing on organizational theory and providing a rich account of prison life, the institution, and key actors, Ashley T. Rubin examines why Eastern's administrators clung to what was increasingly viewed as an outdated and inhuman model of prison - and what their commitment tells us about penal reform in an era when prisons were still new and carefully scrutinized.